Strategi Penguatan Gotong Royong Berbasis Kearifan Lokal dalam Meningkatkan Pengelolaan Wisata Danau Kalpataru - Nur Khalifah, Melati Rahmaningrum; Tambunan, Shuri Mariasih Gietty; Suharjo, Rias Antho Rahmi (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
The main problem in housing complexes is the lack of awareness of mutual cooperation. The aim of this research is to analyze mutual cooperation actions in the Banjar Wijaya residential area in managing the environment. The method used is qualitative analysis, conducting in-depth literature studies and in-depth interviews (purposive sampling) involving the ketua RW, local residents and tourists. The results of this research are the characteristics of residents in the Banjar Wijaya housing cluster, Cluster Italy, Tangerang City, that local residents in these housing complexes tend to be passive, then become active because they receive an example from the RW chairman who raises high awareness of environmental conditions. This is a driving factor for the creativity of Lake Kalpataru tourism economic activities such as improving infrastructure, managing the environment, urban farming and developing tourist destinations for Lake Kalpataru and other events